Association Between the Rate of Diabetes and Quality of Patient Care in Home Health Agencies. Issue 2 (May 2019) - Zikos, Dimitrios; Ogunneye, Yetunde; Delellis, Nailya; Ivanitskaya, Lana
The multitude of comorbidities and disabilities that are prevalent among diabetic patients make their care very challenging for providers. This, in turn, may have a negative effect on measures of patient satisfaction, quality, and outcomes. This study examines the correlation between diabetes ratio as a primary diagnosis in home health agencies (HHAs) with the Home Health Care Consumer Assessment of Healthcare Providers and Systems (HHCAHPS) survey and the Outcome and Assessment Information Set (OASIS) star ratings. Our result indicates that HHAs with a higher proportion of patients with diabetes have lower ratings in health outcomes (bathing, breathing, moving from the bed, moving around, and controlling pain). The association was stronger in the case of diabetic cases with complications.